Renewal, Renaissance, Reformation, or Revolution? Guiding concepts for social transformation in South Africa in the light of 16th century ecclesial reform and deform movements in Europe - Conradie, Ernst M; Sakupapa, Teddy C (Stellenbosch Theological Journal, 2017)
This contribution is based on what may be called a pedagogical experiment in a postgraduate course on the 16th century European Reformations that was offered at the University of the Western Cape in the first semester of 2017. On the basis of a close reading of selected literature on the reformation, this contribution highlights the legacy of 16th century ecclesial movements for Southern Africa. The point of departure is located in the context of a discussion on a range of guiding concepts for social transformation in the contemporary (South) African context. It is argued that the deepest diagnosis of current (South) African discourse may well point to a view that none of the options for a category that may be regarded as more ultimate than justice (as a ‘remedy’) is attractive enough to muster sufficient moral energy without endless further contestations. Without necessarily suggesting what that ultimate maybe, it is suggested that a lack of an appealing notion of what is truly ultimate can undermine any attempts to address inequality (as our diagnosis) in current discourse. This necessarily calls attention to the relationship between the penultimate and the ultimate, and indeed between justification and justice.